The reasons for and influences of unintended teenage pregnancy in Kericho county, Kenya: a qualitative study - Rio Harada; Atsuko Imoto; Louisa Ndunyu; Ken Masuda (BMC, 2024)
Abstract Background Unintended teenage pregnancies are associated with greater health and socio-economic risks for teenage mothers and newborns. In Kenya, the government has declared a target for ending teenage pregnancy by 2030. However, the prevalence of teenage pregnancy has only decreased slightly, demonstrating the need for further efforts. Understanding teenage mothers' own experiences and perspectives is necessary to design appropriate interventions. Methods A community-based qualitative study was conducted from March to May 2023. Two focus group discussions were conducted with community health volunteers and the mothers of teenage girls. Semi-structured interviews were conducted on the case histories of 19 teenage mothers and 18 key informants. Thematic analysis was subsequently performed using MAXQDA 2022. Findings Four major reasons emerged for unintended teenage pregnancies: (1) lack of knowledge or awareness about the human reproductive system, (2) lack of knowledge about family planning (FP), (3) financial challenges, and (4) low access to FP. At the study site, cultural norms and stereotypes, such as "infertility caused by FP," "freedom of sex by promoting FP," and "cultural taboos on having sex before marriage and talking about sexuality," were observed as barriers in promoting FP to teenagers. In addition, teenagers from low socio-economic backgrounds were found to be more vulnerable because they can be easily exploited by men who can afford to provide for some of their basic needs. Regarding the influences of unintended teenage pregnancy on teenage mothers' lives, the 19 cases were classified into four categories: (1) dropping out of school, (2) financial challenges, (3) changing relationships with parents, and (4) no major influence. Crucially, unintended teenage pregnancies negatively influenced most study participants. Continuing education, supportive parental attitudes, positive perceptions of the relationship with the child's father, and having future perspectives were identified as factors mitigating the negative influences. Conclusions Strengthening culturally appropriate comprehensive sexuality education and the school re-entry policy with a supportive environment may prevent unintended teenage pregnancy and mitigate its negative influences. As financial challenges can be both a reason for and a negative influence of unintended teenage pregnancy, economic empowerment interventions are necessary.